2017
DOI: 10.18632/oncotarget.19610
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptors (PPARs) are potential drug targets for cancer therapy

Abstract: Peroxisome-proliferator-activated receptors (PPARs) are nuclear hormone receptors including PPARα, PPARδ and PPARγ, which play an important role in regulating cancer cell proliferation, survival, apoptosis, and tumor growth. Activation of PPARs by endogenous or synthetic compounds regulates tumor progression in various tissues. Although each PPAR isotype suppresses or promotes tumor development depending on the specific tissues or ligands, the mechanism is still unclear. In this review, we summarized the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 60 publications
1
62
0
Order By: Relevance
“…A number of studies showed that PPARγ agonists arrest the cell cycle, thereby inhibiting inhibit cell growth in vitro and in cancer cells inoculated into experimental animals (Law et al, 1996;Altiok et al, 1997;Motomura et al, 2000;Wakino et al, 2000;Itami et al, 2001;Koga et al, 2001;Bruemmer et al, 2003;Dios et al, 2003;Srivastava et al, 2014). Thus, PPARγ agonists are candidates for cancer therapy (Gou et al, 2017). With the placental transcript analyses, we showed that the deletion altered the expression patterns of E2Fs and cyclins, which are determinants for cell cycle staging (Cuitiño et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…A number of studies showed that PPARγ agonists arrest the cell cycle, thereby inhibiting inhibit cell growth in vitro and in cancer cells inoculated into experimental animals (Law et al, 1996;Altiok et al, 1997;Motomura et al, 2000;Wakino et al, 2000;Itami et al, 2001;Koga et al, 2001;Bruemmer et al, 2003;Dios et al, 2003;Srivastava et al, 2014). Thus, PPARγ agonists are candidates for cancer therapy (Gou et al, 2017). With the placental transcript analyses, we showed that the deletion altered the expression patterns of E2Fs and cyclins, which are determinants for cell cycle staging (Cuitiño et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have suggested that c‐Myc, Bcl2, bFGF and VEGF are the targets of PPARγ during cancer cell proliferation . We tested the effects of miR‐27b‐3p on the mRNA expression of these downstream molecules in ATC cells.…”
Section: Resultsmentioning
confidence: 99%
“…In high-FFA diabetic rats, the accumulation of fatty acids, eicosanoids, or oxidized phospholipids activates peroxisome proliferator-activated receptors (PPARs), which are involved in lipid metabolism. PPAR are expressed in three isoforms, namely PPARα, PPARγ and PPARδ, which are encoded by different genes and form a subfamily of the nuclear receptor superfamily (34). The activation of PPARδ in the VSMcs of diabetic patients with elevated levels of FFAs is beneficial to the cardiovascular system due to its effects on lipid metabolism, insulin sensitivity and glucose homeostasis (35,36).…”
Section: Discussionmentioning
confidence: 99%